Upaya Meningkatkan Hasil Belajar Ekonomi Dengan Menerapkan Metode Tutor Teman Sebaya Pada SMA Negeri 1 Palangka Raya - Bayu Nurahma Suharo; Ilham Ilham (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine: learning outcomes and economic learning activities using the Peer Friend Tutor Method in Class Students. The method used in this study is to use a Classroom Action Research (CAR) design that seeks to overcome the problems faced in the current situation. The subjects needed in this study were students of class XI IPS 1 in SMA 1 Palangka Raya, which numbered 40 students. The results of the study show that: (1) the learning activities of the class students are very good. The results of observations of the first cycle of learning activities of students gained a score of 3.03 with good criteria, and the second cycle of activities of students experienced an increase in obtaining a score of 3.81 with good criteria. (2) There is an increase in economic learning outcomes. In the classical pre-test, there were 17.5% of students who completed with an average score of 59.75. After being implemented in the first cycle of students who completed it increased to 67.5% of students who completed classically with an average of 78.12. In the second cycle classically 97.5% of students completed with an average value of 86.25